Sosialisasi Tanaman Obat Keluarga: Pemanfaatan Daun Belimbing Wuluh sebagai Alternatif Penurun Kolesterol Hiperkolesterolemia - Jalung, Ferdinan; Anggriani, Ririn; Umamy, Farida (Jurnal Masyarakat Indonesia (Jumas), 2025)
The purpose of this study was to determine whether ethanol extract can lower total cholesterol levels in mice and to analyze the effect of administering ethanol extract of starfruit leaves at graded doses compared to simvastatin on total cholesterol in mice. The research method used was experimental. Starfruit leaves were extracted using a maceration method with 96% ethanol. ethanol. Organoleptic observations, water and ethanol soluble extract levels, and drying loss were carried out. Then, a test was conducted on the effectiveness of reducing total cholesterol levels from starfruit leaf extract in hypercholesterolemic mice given egg yolk orally with negative control (induction with high-fat food), positive control (simvastatin 2.6 mg/kg BW), treatment one (starfruit leaf ethanol extract 150 mg/kg BW), treatment two (starfruit leaf ethanol extract 300 mg/kg BW), treatment three (starfruit leaf ethanol extract 600 mg/kg BW). Administered in the morning and evening for 7 days.The ethanol-soluble extract test averaged 14%. Given in the morning and evening for 7 days, starfruit leaves have a distinctive, pungent aroma and an unpleasant taste. Ethanol extract of starfruit leaves is very high and dangerous even when cholesterol levels are normal